Total and Bioaccessible contents of Microelements in Multivitamin Formulations Exposed to Consumption in Brazil using in vitro Gastrointestinal Digestion (INFOGEST Protocol) - Abdon Luiz Ornelas Latif; Thaís Luz de Sousa; Laura Beatriz Souza e Souza; Ivana Ferreira Simões; Alex Sander Lopes da Silva; Daniele Cristina Muniz Batista Santos; Aníbal de Freitas Santos Júnior; Clícia Maria de Jesus Benevides (Journal of Trace Elements and Minerals)
Background: Multivitamin formulations (MFs) are used worldwide to meet needs in diets for the purpose of improving health, when necessary. Therefore, evaluating the in vitro micronutrient bioaccessibility by gastrointestinal digestion methods is essential to understand the available fraction of these analytes in the body. Objective: In this study, methods were optimized and validated using the INFOGEST 2.0 protocol for in vitro gastrointestinal digestion and ICP OES to quantify concentrations of 13 trace elements (Al, Ba, Ca, Cu, Fe, Mn, Mo, Se, Sn, Sr, Ti, V, and Zn) in Brazilian MFs. Additionally, it seeks to correlate the levels of elements indicated on the label with the recommended daily values (RDV). Methods: Approximately, 0.75 g of MF sample were digested in a closed digestion block using 2.0 mL of 65 %(m/m) HNO3 + 5.0 mL of ultrapure water + 1.0 mL of 30 %(m/m) H2O2, at 180 °C for 90 min. Microelement bioaccessibility in Brazilian MFs through in vitro gastrointestinal digestion INFOGEST 2.0 and analysis by ICP OES were performed. Results: The range of microelements total contents (µg g-1) in the multivitamin formulations were: Al (11.2 ± 0.2 to 256.0 ± 22.2), Ba (< 0.004 to 1.2 ± 0.1), Cu (11.0 ± 0.9 to 1327.9 ± 25.6), Fe (1373.2 ± 49.7 to 8480.6 ± 146.9), Mn (443.6 ± 3.9 to 2670.7 ± 137.5), Mo (< 0.02 to 29.0 ± 1.4), Se (< 0.01 to 54.7 ± 1.6), Sn (< 0.01 to 15.0 ± 2.4), Sr (< 0.002 to 60.4 ± 0.7), Ti (< 3.0 to 99.3 ± 5.3), and Zn (551.5 ± 21.2 to 3675.5 ± 40.3). Vanadium was below the quantification limit (< 0.02). The results revealed low bioaccessible contents (%) of Cu (0 to 23.8), Fe (0 to 15.7), Mn (0 to 11.4), and Zn (0 to 9.7), emphasizing the importance of regulation and quality control for consumer confidence. Conclusion: The analysis of Brazilian MFs raised significant concerns, as most samples did not reach 50 % of the total declared content. The low mineral release during digestion simulation indicates the need for more effective formulations.